High-viscosity Pickering emulsion stabilized by amphiphilic alginate/SiO2 via multiscale methodology for crude oil-spill remediation. (1st December 2021) - Zhao, Xinyu; He, Furui; Yu, Gaobo; Feng, Yuhong; Li, Jiacheng
Abstract: The separation of crude oil from oily water and collection of the emulsion constituents has attracted significant attention. We demonstrate that the relationships between inherent dynamic factors and the performance of a Pickering emulsion stabilized by SiO2 particles with adsorbed hydrophobically modified sodium alginate derivatives (HMSA), a natural pH-sensitive polysaccharide, can be clarified via a multi-scale methodology. Functionalization of the silica surface with HMSA controls particle dispersibility, as verified by turbidity and stability analyses, the zeta potential, and transmission electron microscopy measurements. The interaction mechanism between HMSA and SiO2 nanoparticles was elucidated by both experimental adsorption measurements and computer simulations, which showed qualitative consistency. The aggregation/disaggregation of HMSA/SiO2 particles achieved by tuning the pH of the solution facilitated reversible dispersibility/collectability behavior. Overall, a high-viscosity Pickering emulsion system based on particle-particle and droplet-droplet interactions, which can be filtered for the recovery of spilled crude oil, was demonstrated. Graphical abstract: The relationships between inherent dynamic factors and the properties of high viscosity Pickering emulsion system for crude oil-spill remediation was investigated by a multi-scale methodology. Unlabelled Image Highlights: High-viscosity emulsion stabilized by alginate derivative (HMSA)/SiO2 was prepared. Interaction of HMSA/SiO2 was elucidated by experiment and mesoscale simulation. The structure-property relationship of emulsion was explored by multiscale approach. Filterable Pickering emulsions could be candidates for crude oil-spills remediation.